KEBERLANJUTAN USAHA TANI MINA PADI DI KALURAHAN SUMBERAGUNG KAPANEWON MOYUDAN DAERAH ISTIMEWA YOGYAKARTA - Mesalia Kriska; Harsoyo Harsoyo; Rezki Putri Sulami; Novam Tri Wikarno Putra; Yenni Kusuma (Universitas Sebelas Maret, 2022)
Mina padi is a rice-fish integrated farming system that could increase agricultural field productivity. By implementing this innovation, agricultural land production could increase, and farmers will benefit from two different commodities, namely rice and fish. The involvement of mina padi farmer groups and support from the agricultural extension officer is needed to achieve maximum results in implementing of Mina padi cultivation. One of many areas that have already been implementing a mina padi farming system in the Special Region of Yogyakarta is Sumberagung Village, Moyudan District. In Sumberagung Village, there are 5 mina padi groups with a total of around 64 members that are still actively running mina padi business. The main aim of this study is to determine the sustainability of mina padi farming in Sumberagung Village, Moyudan District, Sleman Regency. The analytical framework used in this study is the Threats, Weakness, Opportunity, and Strength framework by analyzing the threats, weaknesses, opportunities, and strengths of the Mina padi group business activities. This analysis will provide a sustainable development strategy for the mina padi farming system in Sumberagung Village, Moyudan District. The strategies that would sustain mina padi farming business sustainability are intensifying the mina padi farming field, using the tanam jajar legowo (tajarwo) farming system, and reducing pesticide usage, developing mina padi agritourism, and organizing training for mina padi to the younger generation.